WSPM-System: Providing Real Data of Rotor Speed and Pitch Angle for Numerical Simulation of Downwash Airflow from a Multirotor UAV Sprayer - Hao Zhang (MDPI AG, 2021)
The accurate setting of input parameters in the numerical simulation of downwash airflow from a UAV sprayer is important for acceptable simulation results. To provide real data of simulation parameters (rotor speed and pitch angle) for the numerical simulation of downwash airflow, a wireless simulation parameter measurement system (WSPM-System) was designed and tested in this study. The system consists of hardware and software designed based on Arduino and LabVIEW, respectively. Wireless communication was realized by nRF24L01. The lattice Boltzmann method (LBM) was applied for the numerical simulation of downwash airflow. The results showed that the valid communication distance of the WSPM-System was 100 m, with a packet loss rate of less than 1%. While hovering, the rotor speed dropped by about 30% when the load of the UAV sprayer changed from 16 kg to 4 kg, which resulted in the maximum vertical downward velocity (VVD) on the horizontal detection surface dropping by about 23%. Under forward flight, the rotor speed in the front (n1, n6) and rear (n3, n4) of the UAV sprayer, respectively, showed a negative linear correlation and positive linear correlation with flight speed (R2 > 0.95). Meanwhile, the rotor speed in the middle (n2, n5) was consistent with the rotor speed while hovering under the same load; the pitch angle showed a positive linear correlation with flight speed (R2 > 0.94). A correlation analysis of measured and simulated values of the VVD revealed that the numerical simulation of downwash airflow with the parameters provided by the WSPM-System was reliable (R2 = 0.91). This study confirmed that the input value of the rotor speed in the fluid software needed to be determined according to the application parameters of the UAV sprayer, thus providing a feasible method and system for obtaining real simulation parameters.